Straight Beams Elastically Stressed: Example 1 - Pitarresi, James (McGraw-Hill's AccessEngineering., 2012)
This video illustrates an example in Roarks' Formulas for Stress and Strain on straight beams (common case) elastically stressed. The tensile and compressive stresses in a beam are computed for three different cross-sections.